The Vocal Legacy of Antonio Estévez. Study and Context based on the Critical Edition of his 17 Songs for Voice and Piano (Revista del Instituto de Investigación Musicológica "Carlos Vega", 2025)
This work analyzes and presents the challenges of the critical edition of Antonio Estévez’s 17 canciones para voz y piano. As the official edition (1986) contains editorial inconsistencies that hinder its interpretation. This repertoire has remained overshadowed by Cantata criolla (1954), the composer’s emblematic work. The methodology is based on musical philology and critical editing, following the heuristic, hermeneutic, and ecdotic phases. The editorial principles of Grier, Caraci Vela, and Sans were applied. The musical text was reconstructed using the source Canciones para voz y piano by Antonio Estévez, an unofficial edition published by the composer himself, though with irregular editorial quality. Additionally, calligraphers who worked alongside the composer were interviewed. Among the conclusions, it is highlighted that the critical edition of these songs enhances the accessibility of this repertoire.